2018
DOI: 10.1093/asj/sjy292
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Extended Deep Plane Facelift Technique for Jawline Rejuvenation and Volumization

Abstract: Background Jawline aging is a complex process. We believe loss of posterior jawline definition and volume depletion is an underappreciated factor in the aging face. Objectives The aim of this study was to describe a novel composite, rotational flap modification of an extended deep-plane rhytidectomy. We evaluated long-term efficacy on improving jawline contour and volumization of the posterior mandibular region overlying the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…By lysing the cervical retaining ligaments more advancement and a more posterior suspension site to include the mastoid periosteum is possible. 18 In the patient without an effective decussation of the medial platysma, the author found that platysma bands may again become visible.…”
Section: Posterior Suspensionmentioning
confidence: 99%
See 1 more Smart Citation
“…By lysing the cervical retaining ligaments more advancement and a more posterior suspension site to include the mastoid periosteum is possible. 18 In the patient without an effective decussation of the medial platysma, the author found that platysma bands may again become visible.…”
Section: Posterior Suspensionmentioning
confidence: 99%
“…25 After the myotomy is performed, the distal platysma muscle flap below the myotomy is advanced posteriorly to or beyond the platysma-auricular ligament and sutured into the sternocleidomastoid muscle insertion at the mastoid. 18 It is important Fig. 6 Drawing of anterior platysmaplasty.…”
Section: Patient Evaluationmentioning
confidence: 99%
“…With aging, the cervical spine shortens through compression of vertebral bodies and intervertebral discs, displacing downward the hyoid bone and deep neck soft tissue structures and increasing submental fullness through protrusion of subplatysmal fat, digastric muscles, and submandibular glands [14] . Additionally, the mandible experiences bone resorption and narrowing in both length and width, predisposing to lower facial soft tissue descent and effacement of the inferior mandibular border [11,20] .…”
Section: Skeletal Supportmentioning
confidence: 99%
“…In the absence of microgenia, however, placing a chin implant may actually create an unnatural appearance and should be avoided [1] . A deficient mandibular border can be augmented with fillers, such hyaluronic acid or calcium hydroxylapatite, autologous fat grafting or tissue flaps, and prosthetic implants [20] . For patients with a caudally positioned hyoid bone, the peri-hyoid fascial attachments to the bone may be released in order to allow the latter to migrate superoposteriorly to both deepen and sharpen the cervicomental angle [19,32,37] .…”
Section: A B C Dmentioning
confidence: 99%
“…To optimally correct the jowl and the prejowl sulcus, a facelift technique has to be used that will reposition the midface and lift the jowl containing portion of the superficial musculoaponeurotic system (SMAS). This will improve both the lower face and the neck [28][29][30] (►Fig. 7).…”
Section: Soft Tissue Repositioningmentioning
confidence: 99%